Ciência brasileira nos principais sites de notícias : um retrato colonial - Cardoso, Valérya Próspero (2016)
This essay aims to approach, analyze and critically discuss based on decoloniality thinking the impact of news on Brazilian scientific production in the editorial Science in the main sites of Brazil, being them Estadão, Folha de São Paulo, O Globo and G1. The survey was conducted between December 2014 and January 2015. The documents were organized according to own methodology by which the news were separated noticing the institutions source of the research and where the information was published first. The news were also divided between foreign, national and partnerships (Brazilian researchers with foreigners). The results shown that the sites give preference and space for science produced in other countries over the publication of the national research. It concludes that the media, to give priority to foreign knowledge, enhances the experience of the colonial matrix of power living under a quiet domination Euro-American. This rule is characterized by the feeling of inferiority and dependence on other nations called developed. Thus, the decoloniality concept that the socalled Third World has been fundamentally a consumer of erudition and scholarship of the socalled First World also goes to scientific journalism present in major newspapers in Brazil.